A fuzzy-based optimal control algorithm for a continuous casting process - Mauder, Tomas (Materiali in tehnologije, 2012)
Nowadays, continuous casting is used for processing almost one hundred percent of liquid steel into an intermediate shape. Steel with a poor structure and many defects is not acceptable to final customers, and therefore the producers must put strong emphases on its quality. Many serious steel defects can be eliminated by a preceding computer simulation, optimization and a proper control of the casting process. This paper describes an algorithm that optimizes the control parameters to ensure both a high production rate and a high quality of the products. These controlled parameters are the casting speed and all the cooling rates in the secondary cooling zone. The main principle of the algorithm is to get the surface and core temperatures to the prescribed values corresponding to the required ductility of steel. The whole optimization procedure consists of two separate parts, i.e., the numerical simulation of the process and the decision-making part based on fuzzy logic for modifying the control parameters. By incorporating the fuzzy logic into the optimization process, the algorithm has a very robust behaviour and an easy adaptation for different grades of steel. This algorithm runs in an off-line version and can be used as a preparation tool for a real casting process where the proper setting of the casting parameters is crucial for achieving high-quality products at an economical price.
Keywords: fuzzy optimization; mehka optimizacija; heuristic optimization; hevristična optimizacija; temperature field; temperaturno polje; continuous casting; kontinuirno litje